Herding Behavior Under Markets Condition: Empirical Evidence on the European Financial Markets - Moatemri Ouarda; Abdelfatteh el Bouri; Olivero Bernard (International Journal of Economics and Financial Issues, 2012)
This study presents four main contributions to the literature of behavior herding. Firstly, it extends the behavioral researches of herding of the investors on a developed market and mainly on a European market as a whole. Secondly, we are interested in examination of herding behavior at the level of sectors by using data at the levels of companies. Thirdly, this document estimates the implications of herding behavior in terms of returns, volatility and volume of transaction. Fourthly, the herding behavior is revealed as well during the period of the recent global financial crisis in 2007-2008 and of Asian crisis. Our results reveal a strong evidence of herding behavior sharply contributed to a bearish situation characterized by a strong volatility and a trading volume. The repercussion of herding during the period of the recent financial crisis is clearly revealed for the sectors of the finance and the technology.